Alcohol and Corruption - KODILA-TEDIKA, Oasis; KANYAMA, Isaac Kalonda; AZIA-DIMBU, Florentin (Journal of Advanced Research in Law and Economics; Vol 4 No 2 (2013): JARLE Volume IV Issue 2(8) Winter 2013, 2016)
This study aims at testing the relationship between alcohol and corruption. Using cross-sectional data, we find the nexus to be positive. It follows that the depth of drinking alcohol has a significant positive correlation with the level of corruption.
Keywords: corruption, alcohol, drinkers, institutions